If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -66x + -121 = 0 Reorder the terms: -121 + 6x + -66x = 0 Combine like terms: 6x + -66x = -60x -121 + -60x = 0 Solving -121 + -60x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '121' to each side of the equation. -121 + 121 + -60x = 0 + 121 Combine like terms: -121 + 121 = 0 0 + -60x = 0 + 121 -60x = 0 + 121 Combine like terms: 0 + 121 = 121 -60x = 121 Divide each side by '-60'. x = -2.016666667 Simplifying x = -2.016666667
| 42x^2-69+20=7x^2-8 | | 52-44.7= | | x^3-4x^2+4x-16=0 | | 6c*12=48 | | 33x-33=6 | | -21+8x=59 | | -4x+y=3 | | 760=325+50m | | -32x^3+2x^7=0 | | 200=.20m+120 | | 2x+8=40 | | 3g-9=99 | | 200=.20m | | 6x+29=2x+129 | | 8x-7(-4.0)=2 | | 116-6x=12x+16 | | 2d-(7)=8-(3d) | | 12+6.2= | | 10+6.2= | | 11-10x=49-17x | | (2d)-(7)=(8)-(3d) | | 36-31x=-10x | | 3(6x+3)=15 | | -2(.25+.85)-3y=10 | | 6x+6=-120-8x | | 3x-4(x+1)+10=0 | | 2(-2+x)-(x-4)+4(1+x)=0 | | -14=-(2x+2) | | x^2-3x=-3 | | 1-5x= | | 3f*15=45 | | 112b+4.4c=1000 |